Analisis Komunikasi Organisasi Karyawan pada PT. Proxi Jaringan Nusantara Wilayah Batam - Syailendra, Melanie; Dimyati, Dindin (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to answer how employee organizational communication at PT. Nusantara Network Proxy Batam Region. This research uses organizational communication theory and communication effectiveness theory. Then the research method used is descriptive qualitative with secondary data collection techniques supported by observation and interview techniques. The research results show that employee organizational communication at PT. The Nusantara Network Proxy for the Batam Region shows an egalitarian pattern. This is influenced by individual factors including region, educational background, culture and others, as well as external factors, namely work environment, friendship cycle, mastery of social media and others. This condition affects organizational communication structurally, either vertically, namely communication between strata/positions or horizontally, namely communication between employees in the same job position.